ADAPTASI OSMOTIK TUMBUHAN MANGROVE Avicennia marina (Forsskål) * Vierh. DAN KEDELAI (Glycine max (L.) Merr.) TERHADAP STRES SALINE - Beth Paul Naiola (BERITA BIOLOGI, 2012)
The extent of salinity effect land due to bad agricultural practices and global climate change that could affect the productivity of cultivated plants in agricultural and coastal areas as a result of rising sea levels, encourage the study of cultivated plants resistance to salinity stress. This research is aimed to observe the mangrove Avicennia marina (Forsskål) Vierh., a halophyt, grew up on the beach as a plant model that is able to adapt to saline environment by pumping out the NaCl (sodium pump) and deposited on the leaf surface. On the application of sea water with a multilevel concentrations (0, 25, 50 and 75%) A. marina is able to adjust by changing the osmotic potential in line with the level of concentration of sea water, as an indication of the course of osmotic regulation. Meanwhile, soybean var. Anjasmoro only able to adapt to sea water at a concentration of 25%, equivalent to 150 mM NaCl. This result may be the starting point by breeders and biotecknolo gists in utilizing the potential genes drives the salinity resistance characters in Indonesian mangrove species (especially Avicennia marina) to contrive salinity resistance cultivars of cultivated food plants with better yield.